A Novel Resorbable Composite Material Containing Poly(ester-co-urethane) and Precipitated Calcium Carbonate Spherulites for Bone Augmentation-Development and Preclinical Pilot Trials - Rode, Claudia; Wyrwa, Ralf; Weisser, Juergen; Schnabelrauch, Matthias; Vucak, Marijan; Grom, Stefanie; Reinauer, Frank; Stetter, Adrian; Schlegel, Karl Andreas; Lutz, Rainer (Molecules, 2021)
Polyurethanes have the potential to impart cell-relevant properties like excellent biocompatibility, high and interconnecting porosity and controlled degradability into biomaterials in a relatively simple way. In this context, a biodegradable composite material made of an isocyanate-terminated co-oligoester prepolymer and precipitated calcium carbonated spherulites (up to 60% w/w) was synthesized and investigated with regard to an application as bone substitute in dental and orthodontic application. After foaming the composite material, a predominantly interconnecting porous structure is obtained, which can be easily machined. The compressive strength of the foamed composites increases with raising calcium carbonate content and decreasing calcium carbonate particle size. When stored in an aqueous medium, there is a decrease in pressure stability of the composite, but this decrease is smaller the higher the proportion of the calcium carbonate component is. In vitro cytocompatibility studies of the foamed composites on MC3T3-E1 pre-osteoblasts revealed an excellent cytocompatibility. The in vitro degradation behaviour of foamed composite is characterised by a continuous loss of mass, which is slower with higher calcium carbonate contents. In a first pre-clinical pilot trial the foamed composite bone substitute material (fcm) was successfully evaluated in a model of vertical augmentation in an established animal model on the calvaria and on the lateral mandible of pigs.
CRIS-Team WoS Importer:2021-01-29